Anticholinergics in the treatment of children and adults with acute asthma: a systematic review with meta-analysis. Issue 9 (17th June 2005) - Rodrigo, G J; Castro-Rodriguez, J A
Abstract : Background: Current guidelines recommend the use of a combination of inhaled β2 agonists and anticholinergics, particularly for patients with acute severe or life threatening asthma in the emergency setting. However, this statement is based on a relatively small number of randomised controlled trials and related systematic reviews. A review was undertaken to incorporate the more recent evidence available about the effectiveness of treatment with a combination of β2 agonists and anticholinergics compared with β2 agonists alone in the treatment of acute asthma. Methods: A search was conducted of all randomised controlled trials published before April 2005. Results: Data from 32 randomised controlled trials (n = 3611 subjects) showed significant reductions in hospital admissions in both children (RR = 0.73; 95% CI 0.63 to 0.85, p = 0.0001) and adults (RR = 0.68; 95% CI 0.53 to 0.86, p = 0.002) treated with inhaled anticholinergic agents. Combined treatment also produced a significant increase in spirometric parameters 60–120 minutes after the last treatment in both children (SMD = −0.54; 95% CI −0.28 to −0.81, p = 0.0001) and adults (SMD = −0.36; 95% CI −0.23 to −0.49, p = 0.00001). Conclusions: This review strongly suggests that the addition of multiple doses of inhaled ipratropium bromide to β2 agonists is indicated as the standard treatment in children, adolescents, and adults with moderate to severe exacerbations of asthma in the emergency setting.